The protective effect of Xanthoceras sorbifolia Bunge husks on cognitive disorder based on metabolomics and gut microbiota analysis. (28th October 2021) - Rong, Weiwei; Han, Kefei; Zhao, Zihan; An, Junying; Li, Qing; Bi, Kaishun
Abstract: Aim of the study: The husks of Xanthoceras sorbifolia Bunge mainly used in north China as folk medicine were reported to have potential protective effect on cognitive impairment. However, the mechanism remains unclear. In order to fully understand the mechanism of the protection, a complementary study of the husks was conducted. Materials and methods: The urinary and fecal metabolomics were used to analyze the potential biomarkers by the liquid chromatography-tandem time of flight mass spectrometry, and the16S rDNA technology was applied to conduct the analysis of microbiota species in the fecal samples of the rats, which is a significant influencing factor for the development of cognitive impairment. Results: In metabolomics study, ten potential metabolic biomarkers, which are hippuric acid, kynurenic acid, creatinine, phenylalanine, xanthurenic acid, phenylacetylglycine, succinyladenosine, cresol sulfate, tryptophan 2-C-mannoside and N4-Acetylcytidine in urine, along with two, including isoleucine and phenylalanine in feces, were preliminarily identified, involving multiple pathways such as tryptophan, purine, kynurenine, and phenylalanine metabolism. The perturbation of these metabolic pathways could be related with insulin resistance, oxidative stress, energy metabolism deficit and neuroinflammation, which were risk factors to cause cognitive impairment. In gut microbiota analysis, the relative abundance of c_Bacteroidia, c_Alphaproteobacteria, f_Prevotellaceae, f_Sphingomonadaceae, f_Burkholderiaceae, g_Prevotellaceae_NK3B31_group and p_Bacteroidetes was significantly changed in the rats with cognitive impairment. Spearman's analysis showed obvious correlation between the metabolites and the microbiota species. In the rats with pretreatment of the husks extract, metabolites maintained a relative normal level, and the husks extract could regulate the gut microbiota, especially f_Prevotellaceae and g_Prevotellaceae_NK3B31_group, indicating the effect of the husks on the metabolic pathways via GMs. Such amino acids as isoleucine and phenylalanine failed to show any significant correlation with the microbiota species, indicating that the husks exhibited the potential protective effect through gut microbiota and other pathways. Conclusions: The husks extract could improve the intestinal microenvironment, and the stability of intestinal microenvironment was associated with normality of tryptophan, purine, kynurenine and phenylalanine metabolic pathways etc, which probably had an effect on cognitive function. This complementary work suggested that gut microbiotas were potential targets of the husks to exert its effect on cognitive impairment. Graphical abstract: Image 1